Social Support Buffers the Impact of Depressive Symptoms on Life Satisfaction in Old Age. Issue 2 (14th March 2016) - Adams, Tangeria R.; Rabin, Laura A.; Da Silva, Valdiva G.; Katz, Mindy J.; Fogel, Joshua; Lipton, Richard B.
ABSTRACT: Objective : Life satisfaction is an important component of overall well-being and declines in life satisfaction are related to adverse health outcomes and mortality. The current study investigated the association of various psychosocial and health-related factors to life satisfaction in older adults as well as the role of social support in moderating these relationships. Methods : 237 non-demented community-dwelling older adults (aged 70 and above) from the Einstein Aging Study completed self-report measures tapping the variables of interest. Results : Lower levels of depressive symptoms, less perceived stress, higher levels of social support, and better self-perceived general health were significantly associated with higher life satisfaction. Additionally, social support buffered the adverse impact of depressive symptoms on life satisfaction where more depressive symptoms were associated with much lower life satisfaction at low levels of social support than at high levels of social support. Conclusions : Findings highlight the beneficial moderating impact of social support for depressive symptoms as it relates to life satisfaction. We discuss study implications, future research directions, and possible interventions that involve boosting social support in at-risk older adults.